Utilization of Sea Fish Consumption (As a Source of Nutritional Products) to Improve the Health of Elementary School Students, High School, Vocational Schools and Islamic High Schools (LITERATURE REVIEW) - Soeandi Pratama; Azhari Umar Siregar; Percaya Hia (Professorline, 2025)
Indonesia has abundant fishery resources, but the level of fish consumption among school children is still low. This study aims to review the literature related to the utilization of marine fish consumption, especially tuna, in improving the health and learning achievement of students from elementary school to high school/vocational school/Islamic high school. Marine fish, especially tuna, are rich in protein, omega-3, DHA, and EPA which play an important role in brain development and endurance. Studies show that regular fish consumption can improve memory, focus on learning, and prevent stunting in children. However, low education, access to quality fish, and children's preference for fast food are the main challenges. Various government programs such as the Gerakan Memasyarakatkan Makan Ikan (GEMARIKAN) have been implemented to increase fish consumption among students. This study proposes innovative strategies such as diversification of fish processing in a form that is more attractive to children and more intensive education about the benefits of fish consumption for health. The results of this study are expected to provide recommendations for agency/institution policies in increasing fish consumption in educational environments in order to create a healthier and smarter generation.